Predictor Factors of Continuous Positive Airway Pressure Failure in Preterm Infants with Respiratory Distress - Winda Intan Permatahati; Amalia Setyati; Ekawaty Lutfia Haksari (SAGE Publishing, 2021)
Respiratory distress contributes significantly to mortality, and morbidity in preterm infants. The incidence of nasal continuous positive airway pressure (CPAP) failure is remarkably high. There are limited data available regarding nasal CPAP failure in Indonesia, and this study is expected to be a reference in taking preventive measures to reduce mortality and morbidity in preterm infants. To determine predictive factors of nasal CPAP failure in preterm infants with respiratory distress. A retrospective cohort study was conducted in preterm infants with respiratory distress at the Neonatology ward of Dr. Sardjito Hospital during January 2017-July 2019. Chi-square or Fisher's exact tests, followed by multivariate logistic regression analysis with backward method, was used to identify factors contributing to nasal CPAP failure. A total of 150 infants were included in this study. Fifty-three (37.8%) infants had nasal CPAP failure. Bivariate analysis showed birth weight <1000 g, singleton, APGAR score 4-7, premature rupture of membrane (PROM), Downes score, and initiation of fractional concentration of inspired (FiO 2 ) requirement were all risk factors of nasal CPAP failure. However, only birth weight <1000 g ( P  = .022; OR 2.69; CI 95% 1.34-5.44), initial Downes score ( P  = .035; OR 2.68; CI 95% 3.10-24.11), and initiation of FiO 2 requirement ≥30% ( P  = .0001; OR 3.03; CI 95% 2.04-4.50) were significant predictors for nasal CPAP failure by multivariate analysis. Birth weight <1000 g, singleton, initial Downes score, and initiation of FiO 2 requirement >30% were significant predictors of nasal CPAP failure in preterm infants with respiratory distress.